VARIASI SUHU AIR PADA PENGADUKAN TERHADAP KADAR ASAM SIANIDA DAN MUTU MINYAK BIJI KARET (Hevea brasiliensis) - Yosep Agustiar H; Usman Pato; Akhyar ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Rubber seed is not utilized optimally nowdays. The alternative method to utilize the rubber is to be used as oil source. This research was aimed to obtain optimal temperature in the agitation on the cyanide acid content and quality of rubber seed oil. This research was conducted by using Completely Randomized Design experiment with four treatmens and four replications which followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatmens in this research were agitation with temperature of 70°C, 800C, 900C and 1000C for 1 hour. The results of study show that the higher temperature in the agitation significantly decreased the average content of cyanide, but increased the peroxide, acid and saponification values. Based on the results obtained, the best treatment was P4 treatment (agitation with temperature of 100°C for 1 hour) with cyanide acid content 1.56 ppm, acid value 3.19 mg KOH/g, saponification value 175.31 mg KOH/g, density 0.90 g/ml and peroxide 2.00 Mek O2/kg. Keywords: agitation, rubber seed, cyanide acid, oil.